AB0311 Superiority of Ultrasound over Clinical Examination in Detecting Tenosynovitis in Rheumatoid Arthritis. (9th June 2015) - Hamdi, W.; Miladi, S.; Cherif, I.; Zouch, I.; Kaffel, D.; Kchir, M.; Chelli, M.; Ladab, F.
Abstract : Background: In rheumatoid arthritis (RA), tendon pathology is a well-recognized, but underestimated aspect of the disease, which may lead to irreversible functional impairment and consequent disability. Clinical joint examination is less time-consuming than ultrasound (US) but it may misdiagnosis tenosynovitis (TS). Objectives: The aim of this study was to compare clinical assessment of tenosynovitis detection with US examination. Methods: A cross sectional study was performed including patients followed-up for active recent RA (RA <2 years, DAS28 >2, 6). Clinical examination was performed by a rheumatologist seeking signs suggestive of flexor of extensor TS. US was performed by an experienced radiologist blinded to clinical data. All tendons of the hands were scanned in the transverse view from the more proximal to the more distal portion at the tracts surrounded by synovial sheath. Totally 140 hands were assessed. Results of clinical examination were compared to US findings. The difference is considered significant if the P>0, 05. Results: Seventy patients were recruited, (56 females, 14 males). The mean age was 53 years-old [24-74 years-old]. The mean duration of the disease was 10 months [3-24 months]. The RA was active with a median DAS28 5, 46 ranging from 2, 91 to 7, 81. Physical examination highlighted TS in 53 (38%) hands, it was bilateral in 50%. Flexor tendons were the most affected (52 hands). Both flexor and extensor tendons were detected affected in 4 hands. US showed TS in 89 (65%) patients. Flexor tendons showed US activity in 80 hands and extensor tendons in 78 hands. US revealed a significant high frequency of TS over clinical examination (p=0, 02). The sensitivity of US to detect TS was 80.3% and the specificity was 50, 4%. Conclusions: The rationale of using US relies on the fact that physical examination provides only limited information on the presence of tenosynovitis. Since TS can be source of functional disagreement, US should be focused, in addition to analyze synovitis, on tendons in RA. References: Emilio Filippucci, Alessandra Gabba and al. Hand Tendon Involvement in Rheumatoid Arthritis: An Ultrasound Study. Seminars in Arthritis and Rheumatism 2012;41:752-60. Backhaus M, Kamradt T and al. Arthritis of the finger joints: a comprehensive approach comparing conventional radiography, scintigraphy, ultrasound, and contrast-enhanced magnetic resonance imaging. Arthritis Rhem. 1999;42:1232-45. Szkularek M, Court-Payen M and al. Interobserver agreement in ultrasonography of the finger and toe joints in rheumatoid arthritis. Arthritis Rheum.2003;48:955-62. Disclosure of Interest: None declared